The impact of affective disorders on self-assessment of the quality of life in patients with chronic coronary artery disease - E. V. Lebedeva; E. D. Schastnyу; T. G. Nonka; E. O. Nalesnik; A. K. Surovtseva; S. N. Vasilieva; A. N. Repin (Бюллетень сибирской медицины)
Aim. To determine the differences in self-assessment of social functioning by patients with chronic coronary artery disease (CAD), depending on the presence of comorbid affective disorders (ADs).Materials and methods. Using the Social Adaptation Self-Evaluation Scale (SASS), which makes it possible to assess the degree of social functioning and satisfaction with various aspects of social life, we studied the features of the social functioning of heart hospital patients with chronic CAD with (n = 248) and without AD (n = 291). In 290 patients (average age 56.6 ± 6.7 years) with chronic CAD, chronic ADs (45%) were revealed; depressive episodes (DEs) were diagnosed for the first time in 24% of patients, and 24.5% of patients had recurrent DEs. Bipolar disorder was found in 6.5% of cases. Qualitative and quantitative parameters were investigated using the Mann – Whitney U test and Student’s t-test. To assess the frequencies, the Pearson’s chi-squared test was used.Results. The mean total SASS score in the patients with chronic CAD with AD corresponded to difficult social adaptation (33.7 [29.5; 39]), while the patients without AD had good social adaptation score of 40.8 ± 6.3 (p < 0.05). In the group without AD, patients with normal social adaptation prevailed (n = 215; 73.8%), while patients with AD more often had difficulties with social adaptation (n = 148; 59.7%). In the CAD patients, depending on the presence of AD, the frequency of disturbances in various spheres of social adaptation differed: employment, interest in and pleasure from activities, disposition of income, pleasure from and interest in seeking information, social support (p = 0.001).Conclusion. Higher frequency of pronounced impairment in social functioning in patients with chronic CAD with AD determines the need for taking this fact into consideration when planning rehabilitation measures in this group of patients.